No need for new natural gas pipelines and LNG terminals in Europe - Franziska Holz; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Natural gas could play an increasing role in the German energy system following the coal exit decided in July 2020 by the German parliament. However, natural gas has no climate benefit compared to coal. What is more, Europe risks to become a battle-ground for the conflict between Russia and the United States. The construction of the Baltic Sea pipeline Nordstream 2 has set in motion a downward spiral of sanctions and counter-sanctions. US liquefied natural gas (LNG) exports compete with Russian gas exports to Europe. While German and European policy makers debate about an appropriate reaction to the US sanctions, we ask which role will US LNG be able to play in the European natural gas market. Model results by DIW Berlin pro-vide first answers. In the long run, however, the European climate policy commitments will lead to a phase-out of fossil natural gas in the wake of the energy transition in the next decades.
Keywords: 330